2004
DOI: 10.1002/anie.200353084
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Catalysis with Bimetallic Complexes: Robust and Efficient Catalysts for Atom‐Transfer Radical Additions

Abstract: A radical alternative? Two highly efficient catalysts for atom‐transfer radical additions were discovered in a parallel screening of bimetallic complexes. Both catalysts contain a rhodium‐centered fragment (blue), which is connected through three chloro bridges to a ruthenium‐centered fragment (red).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 71 publications
2
54
3
Order By: Relevance
“…This rearrangement is most likely the result of the increased steric requirements of the octahedral (ppy) 2 Rh fragment, which make a trans geometry energetically less favorable. With 2.527 (4) A and 2.551(4) A, the Rh III -Cl bond lengths of complex 6 are significantly longer than what was found for the Rh I -Cl bond lengths of complex 5. As it is expected for a complex with two AsPh 3 ligands in cis position, the octahedral geometry around the Ru III center is slightly distorted with As1-Ru1-As2 ¼ 105.24(7)°.…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…This rearrangement is most likely the result of the increased steric requirements of the octahedral (ppy) 2 Rh fragment, which make a trans geometry energetically less favorable. With 2.527 (4) A and 2.551(4) A, the Rh III -Cl bond lengths of complex 6 are significantly longer than what was found for the Rh I -Cl bond lengths of complex 5. As it is expected for a complex with two AsPh 3 ligands in cis position, the octahedral geometry around the Ru III center is slightly distorted with As1-Ru1-As2 ¼ 105.24(7)°.…”
contrasting
confidence: 78%
“…1) [1,2]. The structurally related Rh III -Ru II complex 2 is able to efficiently catalyze the oxidation of secondary alcohols using 2-butanone as the oxidation agent [3] and the Rh IRu II complex 3 was shown to be a very active and robust catalyst for the atom transfer radical addition of CCl 4 to olefins [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kharasch et al reported the addition of carbon tetrachloride or chloroform to C=C double bond of alkenes in the presence of peroxide [22]. The Kharasch reactions have been studied in homogeneous systems by using iron and copper chlorides [23][24][25][26], ruthenium complexes [27][28][29][30], palladium complex [31], nickel pincer complex [32,33], rhodium-ruthenium bimetallic complex [34], and Eu(OTf) 3 [35].…”
Section: Kharasch Addition Reactionmentioning
confidence: 97%
“…5 However, it is highly air sensitive while the initiation requires oxygen whose amount is difficult to control. Other tin-free initiators, including peroxides such as dilauroyl peroxides, 6 water-soluble azo compounds, 7 copper, 8 chromium(II) acetate, 9 bimetallic Rh-Ru complexes, 10 and Mn 2 (CO) 10 , 11 are less commonly adopted due to either the harsh conditions required or the lack of generality. It is therefore highly desirable to develop novel tin-free initiators that are safe and widely applicable.…”
mentioning
confidence: 99%